Деякі особливості оподаткування суб’єктів господарювання в умовах воєнного стану - Дмитрик, О. О.; Казмірук, К. О. (НДІ ПЗІР НАПрН України, 2022)
У статті досліджено особливості оподаткування суб’єктів господарювання в умовах воєнного стану. В умовах повномасштабної війни, досить важливо, щоб економіка продовжувала ефективно функціонувати. Відповідно до цього, виникає необхідність адаптації податкового навантаження і правил до воєнних умов, для сприяння бізнесу в умовах війни. Зазначено про те, що з початком повномасштабного вторгнення військ рф на нашу територію 24 лютого 2022 року, функціонування всього суспільного та державного механізму України зазнало вимушених змін. Такі зміни не оминули й сферу діяльності суб’єктів господарювання, зокрема оподаткування їх діяльності. Наголошено на тому, що з 01 квітня 2022 року була введена в дію нова модель оподаткування, яка діє в умовах воєнного стану. Вона передбачає трансформацію спрощеної системи оподаткування, обліку та звітності, встановлення додаткових можливостей для суб’єктів господарювання при обранні спеціального режиму оподаткування, зміну підходів до справляння податку на додану вартість. Водночас наголошено на існуванні відповідних проблем, наприклад, це стосується положення про звільнення від сплати податку на додану вартість стосовно перехідних залишків необоротних активів. Як висновок, наголошено на тому, що запроваджені податкові зміни мають стабілізаційний, стимулюючий характер, дають можливість суб’єктам господарювання економити кошти на сплаті податків та інвестувати їх у подальшу господарську діяльність і таким чином підтримувати та розвивати її. Водночас суб’єкти господарювання мають підтримувати українську економіку та за можливості сплачувати податки та наповнювати бюджет, щоб держава виконувала свої функції. У перспективі необхідно застосувати оперативну дерегуляцію та оновити державну політику у напрямку податкової та митної сфер. Problem setting. The creation of an effective system of taxation of business entities is one of the main conditions for the effective functioning of the country’s economy and finances, in addition to the fact that the state ensures the redistribution of the gross domestic product and forms centralized and decentralized funds that affect not only the state’s ability to perform its functions, but also and economic status of economic agents. It is precisely in connection with this that, when forming the tax system, the state must take into account the world experience of its construction on generally accepted principles. Analysis of recent researches and publications. The works of such legal scholars and economists as V.O. Ryadinska, K.O. Tokareva, D.A. Kobylnyk, M.P. Kucheryavenko were devoted to the issue of taxation of economic entities, including under martial law. Ovcharenko A.S., Melnyk T.Y., Ivanishyna O.S., Demidenko L.S. and other. Target of the research is to clarify the peculiarities of taxation of business entities under martial law and to determine the main features and problematic issues of such taxation under martial law. Article’s main body. The article examines the peculiarities of taxation of business entities under martial law. It was noted that with the beginning of the full-scale invasion of Russian troops on our territory on February 24, 2022, the functioning of the entire social and state mechanism of Ukraine underwent forced changes. Such changes did not bypass the sphere of activity of business entities, in particular, the taxation of their activities. It is emphasized that from April 1, 2022, a new taxation model, which operates under martial law, was put into effect. It provides for the possibility of business entities to choose a special taxation regime. The introduced special taxation regime provides that taxpayers of the third group will pay a single tax of 2% of income. However, it is not enough to ensure the problem of VAT settlement from the book value of inventory balances, noncurrent assets, since the provisions on the exemption from VAT taxation of transitory balances of non-current assets have not been clarified, because before that, in the event of a change from the general taxation system to a simplified one, the VAT payer will be required to calculate tax liabilities for the following balances. Conclusions and prospects for the development. As a conclusion, it is emphasized that the introduced tax changes enable business entities to save money on paying taxes and invest them in further economic activity and thus support and develop it. At the same time, business entities must support the Ukrainian economy and, if possible, pay taxes (on a voluntary basis) and fill the budget so that the state can perform its functions. In the future, it is necessary to implement operational deregulation and update the state policy in the direction of tax and customs spheres.
Keywords: суб’єкт господарювання; податкова система; оподаткування; єдиний податок; воєнний стан; спрощена система оподаткування; business entity; tax; martial law; simplified system; legal entity; individual entrepreneur; new model of taxation